A Review Based Study for Evaluation of Various Blended Learning Techniques in the Educational Domain - Sheshasaayee, Ananthi; Gayathri, M (International Journal of Computer Sciences and Engineering, 2025)
In today’s scenario blended learning is becoming more common in a very wide range of learning environment. Blended learning is a combination of traditional (face –to-face) learning and online digital media learning. Blended learning is also termed as hybrid learning or mixing mode instruction. Blended learning is helpful in the presence for both teachers as well to students. Blended learning uses and online technology is not just a supplement, but a transform to improve the learning process. In a blended-learning course, students might attend a class taught by a teacher in a traditional classroom and also as an independent online classroom. This type of learning approach ensures the learner in engaging and driving his or her individual learning experience. The benefit of blended learning is time saving, cost reduction and flexible. This paper presents the review of various types of blended learning model and types of evaluation such as formative and summative evaluation.